Expectations and Disappointments of Industrial Innovations - Halevi, Gideon (Lecture Notes in Management and Industrial Engineering, 2017)
The Integrated Manufacturing System (IMS), Group Technology, Numerical Control, and Computer Aided Design (CAD) were four outstanding innovations that were one-time milestones of scientific industrial management. This book describes the expectations and disappointments of the common pitfalls of these ingenious ideas, which leads to understanding of their gradual disappearing, and proposes a way to restore these methods for long term utility and value. The first three innovations dominated the industry till the mid-1970s. Surprisingly, the reason for them being replaced is the same: research of the "routine" was misleading regardless of its ingenuity. In the fourth case, CAD does not support CAPP (Computer Aided Process Planning) and thus Numerical Control could no longer support developments of a system such as a flexible and automated factory. However, they incorporate many features in a specific resource instead within a manufacturing system. CAD technology and machiningcenters remain remarkable as a specific (unique) manufacturing resource. This work proposes ways to revive these innovations for the future. Innovation is a driver for the development of new products and production methods. It should be an integral part of a system and not pursued for its own sake. This volume shows, explains, and remedies this by treating these interesting examples. .